A Psycholinguistic study on slips of the tongue made by Jokowi at Ecosperity Week 2023 - Lestari, Ayu septa; Sastika Seli; Dewi Syafitri (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aimed to analyze the types and the dominant type of slip of the tongue made by Jokowi at Ecosperity Week 2023. The method applied was descriptive qualitative. The subjects of this research is Jokowi’s speech. The data were taken from video of Jokowi’s speech at Ecosperity Week 2023, obtained from YouTube. The collected data were transcribed and analyzed based on the types of slip of the tongue proposed by Altiparmark and Koruoglu (2014). The result of the research were 15 slips of the tongue found in the utterances by Jokowi: 7 deletions, 5 additions, 1 subtitutions, I anticipations, and 1 misdevations. Therefore, Jokowi produce 5 types slip of the tongue and deletions was the dominant types occured.